Analisis Kesulitan Siswa Dalam Menyelesaikan Soal Materi Trigonometri Ditinjau Dari Gaya Belajar - Wijayanti, Melinda Dwi; Nalurita, Ika Victoria (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2024)
According to the OECD, the 2018 PISA results state that 71% of Indonesian students experience difficulties when faced with conditions that require them to solve problems by applying mathematical concepts, so they fail to achieve minimum competitive ability in mathematics. Based on the observations of researchers, there are MAN 1 Gresik students who have difficulty in solving trigonometric problems because they think that this material is too much memorizing formulas. This study used learning style questionnaires, test questions, and interviews to collect data in order to find out students' difficulties in solving trigonometry problems in terms of students' learning styles. The results obtained from this study include: 1) The difficulties of auditorial subjects are the inability to remember the steps of proving trigonometric identities; the basic concepts of trigonometric comparisons and the Pythagorean Theorem, unable to recognize mathematical angle symbols, less careful in calculating powers and calculating fractions, and the inability to draw conclusions. 2) The difficulties of kinesthetic subjects are the inability to remember the steps of proving trigonometric identities and the Pythagorean Theorem, the inability to recognize mathematical angle symbols, and less careful in calculating powers and calculating fractions; 3) The difficulties of visual subjects are the inability to remember the steps of proving trigonometric identities, the inability to recognize mathematical angle symbols, and the inability to draw conclusions.